If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8z-z=-1+5z-3-2
We move all terms to the left:
8z-z-(-1+5z-3-2)=0
We add all the numbers together, and all the variables
8z-z-(5z-6)=0
We add all the numbers together, and all the variables
7z-(5z-6)=0
We get rid of parentheses
7z-5z+6=0
We add all the numbers together, and all the variables
2z+6=0
We move all terms containing z to the left, all other terms to the right
2z=-6
z=-6/2
z=-3
| 8x-40=4x+12 | | 11x-10x=4 | | 3+5a/2=9 | | 4x^2+8x-9=131 | | 4/x-10=6 | | 80x×0.15(90)=70x+70×90 | | -w^2+3w+50=0 | | 4b=2b+27 | | 5x+4(-3)=17 | | 4^2x+1=512 | | 2n³+n²=0 | | 5n+18=33 | | 9j-29=43 | | 9x-5x+2=x-8+10 | | |x-3|=3 | | (5x+5)=5x-500 | | 5l-13=47 | | 900+0.25x=1 | | 3l+9=54 | | 5x−3(4x−8)=−11 | | 5b+6=20 | | j/5=5/125 | | 4g+3=55 | | 19x=2,0 | | 8x=81+41 | | 15=+4(5y-10)= | | 15=+4(5y-10) | | 5x=41+21 | | 8(^2x+3)=48 | | 2w-12=42 | | 6t=75-15 | | 8c-7(c-3)+4=16 |